1989
DOI: 10.1007/bf01313819
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies with neutralizing activity to equine herpesvirus 1

Abstract: Seven monoclonal antibodies with neutralizing activity to equine herpesvirus-1 were produced. These recognized either an 81 kD or an 88 kD viral glycoprotein. Some of the antibodies were shown to protect hamsters in a passive immunization experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This indicated that neutralizing antibodies, which were in part dependent on complement, were elicited by the truncated gpl4 expressed in insect cells but not by that produced in E. coli. The higher antibody titres in the presence of complement were not surprising since the activity of several MAbs against gpl4 is also dependent on the addition of complement (Shimizu et al, 1989). The neutralizing antibody titres described here are in agreement with those obtained by Guo et al (1990) after immunization of guinea-pigs with recombinant vaccinia virus expressing gpl4, which was nonetheless capable of protecting against lethal EHV-1 challenge in Syrian hamsters.…”
Section: Short Communication 2045supporting
confidence: 81%
See 1 more Smart Citation
“…This indicated that neutralizing antibodies, which were in part dependent on complement, were elicited by the truncated gpl4 expressed in insect cells but not by that produced in E. coli. The higher antibody titres in the presence of complement were not surprising since the activity of several MAbs against gpl4 is also dependent on the addition of complement (Shimizu et al, 1989). The neutralizing antibody titres described here are in agreement with those obtained by Guo et al (1990) after immunization of guinea-pigs with recombinant vaccinia virus expressing gpl4, which was nonetheless capable of protecting against lethal EHV-1 challenge in Syrian hamsters.…”
Section: Short Communication 2045supporting
confidence: 81%
“…This precursor is then proteolytically cleaved into a 53K to 55K (58K) and a 75K to 77K subunit which form a disulphide-linked 145K heterodimer in the mature virion (Sullivan et al, 1989;Meredith et al, 1989). The gpl4 is known to be an important target of the humoral immune response since several monoclonal antibodies (MAbs) directed against EHV-1 gpl4 showed virus-neutralizing activity and conferred passive protection in the Syrian hamster model (Allen & Yeargan, 1987;Stokes et al, 1989;Shimizu et al, 1989). Attempts to express EHV-1 gpl4 have been undertaken previously.…”
mentioning
confidence: 99%
“…In a separate investigation using Syrian hamsters [25] all three MAbs which mediated protection were also of Ig G2 a isotype. However, there has been one report of protection by an IgG1 isotype [22] and passive protection studies in other herpesviruses using larger panels of MAbs have not demonstrated a correlation between isotype and passive protection [6,17]. Also, the in vivo half-live of individual MAbs used in this study have not been determined.…”
mentioning
confidence: 76%
“…In addition, monoclonal antibodies (MAbs) directed against both gp 13 and gp 14 passively protect hamsters against EHV-1 infection [22,25,26]. Neutralizing MAbs to both of these glycoproteins have also been described 1,4,22,23], although detailed epitope analysis to determine the topographical relationship of epitopes and delineation of relevant antigenic sites has not been reported. Similar studies with other herpesviruses have been important in the identification of immunologically important antigenic sites, some of which may consist of single epitopes and others of multiple overlapping epitopes [16,18].…”
mentioning
confidence: 97%
See 1 more Smart Citation